EFEKTIVITAS METODE PEMBERIAN TUGAS PADA PEMBELAJARAN IPS KELAS VA DI SDN PORIS GAGA 3 KOTA TANGERANG - Ailia, Nia (JTIEE (Journal of Teaching in Elementary Education), 2021)
The aim of this research was to find out the effectiveness of the assignment method and the types of assignments given by the teacher in social studies class VA at SDN Poris Gaga 3, Tangerang. This research using descriptive qualitative research method. The data were collected through interview, observation and documentation. Data were analyzed with data reduction, data display and verification. The results of this research indicate that by using the assignment method in VA class social studies learning has been effective. This is because giving assignments by online, students are faster in understanding the material presented by the teacher, achieving learning objectives and giving, processing and collecting assignments can be done quickly. Giving assignments also train students sense of responsibility, independence and discipline in doing assignments given by the teacher. The types of tasks that given by teacher to students are in orally and written.